EVALUATING THE DISTANCE LEARNING IN THE PANDEMIC ERA: A CASE STUDY AT FINANCIAL EDUCATION AND TRAINING AGENCY MAKASSAR - Azwar Iskandar; Achmat Subekan (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
The objectives of this research were to: (i) evaluate the trainees’s satisfaction on trainers and training performance; (ii) evaluate learning gain or the improvement of trainees’s skills, knowledge, and attitude after training; and (iii) know the significant obstacles that reduced the effectiveness of training. This study was conducted by using Kirkpatrick Evaluation Model through questionnaires, interviews, and descriptive statistics method. This research revealed that: (i) the overall aspect of the implementation evaluation assessed by participants was in Good category although it could not meet the level of participants’ expectations. It could be seen from the ratio of the average total perception/reality and the average of important which were below 100%. On the other hand, it was found that the trainers were been able to meet the participants’ expectations with the category of Very Good; (ii) the results of the evaluation analysis at Level 2 (learning gain) indicated that most of the participants graduated with Good predicate and got an increased score. Thus, it could be asserted that the participants gained additional knowledge after attending the training; (iii) there were some obstacles faced by participants in attending the training although in general the evaluation results showed good results. In terms of administration, it was found that participants generally complained about inadequate internet quality in some areas. Meanwhile, based on the trainers aspect, it was revealed that participants generally gave suggestions for trainers to add case studies and to raise the latest issues in handling the problems related to training materials.